2021
DOI: 10.9756/int-jecse/v13i2.211074
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Learning Orientation in Ma'had and Islamic Boarding Schools, and its Relevance to the Need for Human Resources with Language Skills in the Globalization Era

Abstract: The problem and the aim of the study: The demand for human resources with language skills in the globalization era is very high. This is because many companies require active and passive language skills as the main criteria for workforce recruitment. In Indonesia, Arabic teaching institutions are categorized into two forms, namely those that teach with communication skills orientation (ma'had) and those with an orientation to understand the concept as an Islamic knowledge source (Islamic boarding schools). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…In line with these data, students are of the view that Arabic taught through the curriculum is set to be accommodated in the kitab kuning curriculum. This is in line with a study by Ritonga et al that students graduated from presantren are more dominant in the grammatical aspects of Arabic (Ritonga, Widodo, et al, 2021). High knowledge of Arabic grammar is based on the dominance of learning the kitab kuning in pesantren.…”
Section: Resultssupporting
confidence: 90%
“…In line with these data, students are of the view that Arabic taught through the curriculum is set to be accommodated in the kitab kuning curriculum. This is in line with a study by Ritonga et al that students graduated from presantren are more dominant in the grammatical aspects of Arabic (Ritonga, Widodo, et al, 2021). High knowledge of Arabic grammar is based on the dominance of learning the kitab kuning in pesantren.…”
Section: Resultssupporting
confidence: 90%
“…This is different from a study by Ansyah et al confirmed the importance of maintaining the learning system with the Kaji duduak system in Islamic boarding schools, because the system has made learning patterns in Islamic boarding schools leading students able to read books well (Ansyah et al, 2020). Meanwhile, the researchers saw that the purpose of learning foreign languages and Arabic, in particular, is to help students achieve the four language skills as needed in the industrial revolution era (Albantani & Madkur, 2019;Ritonga, Widodo, et al, 2021).…”
Section: Arabiyâtmentioning
confidence: 72%
“…Foreign language has been a crucial element in the current progressive Islamic education, especially in the Pesantren or Islamic Boarding Schools (hereinafter abbreviated as IBS) curriculum trend, and many IBS have set foreign language competency as a marketing strategy and a part of the education goals of the Islamic school institutions. It can be seen in the current empirical research on IBS, which cannot be separated from the development of language planning and policy in its language education strategy (Abdurrizal et al, 2022;Dariyanto et al, 2022;Fattah et al, 2022;Habiburrahim et al, 2022;Lestari & Pratolo, 2019;Ritonga et al, 2021;Ritonga & Nurdianto, 2022). In the case of general education in Indonesia, common foreign languages taught in Indonesia are Arabic, English, Mandarin, and French (Abduh & Rosmaladewi, 2019;Hamied & Musthafa, 2019;Kohler, 2019;Saud & Abduh, 2018;Zein, 2020).…”
Section: A Introductionmentioning
confidence: 99%
“…Thus, Arabic is an important language because the Muslim Holy Book, the Qur'an, is in Arabic. However, the current movement in Islamic education in Indonesia has shown how Arabic has changed from a literature language to a communication-based language, containing an economic and strategic role in addition to its sacred role, and how the educational institution has focused on speaking acquisition (Fattah et al, 2022;Redkin & Bernikova, 2016;Ritonga et al, 2021;Ritonga & Nurdianto, 2022;Wekke, 2015).…”
Section: A Introductionmentioning
confidence: 99%